DEVELOPMENT OF OFFICIAL CATHOLIC MORAL TEACHINGS ON MARRIAGE DURING THE PAST 50 YEARS - Tirimanna, Vimal (Asian Horizons, 2015)
A clear sign of the presence of the Holy Spirit in the Church as promised by Jesus is the gradual development of her own doctrine so that generations of various ages could understand clearly God’s revelation in and through the Church. Such development or growth is also a sign that the Church is a living organism. The Church’s official teachings with regard to issues linked with marriage are no exception to such development. In this article, an effort is made to highlight some of the main developments in such teachings during the past 50 years, first with regard to marriage in general, and then, under eight specific themes.